Income Mobility in the United States and Germany: A Comparison of Two Classes of Mobility Measures using the GSOEP, PSID, and CPS - Andrew J. Houtenville (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
The United States is often considered to be more free-wheeling and mobile than Germany; however, previous cross-national studies of income mobility find the oppositeis true. This paper investigates these surprising results and finds that they are confirmed when income mobility is measured by changes in the positions of individuals inthe income distribution - members of former West German households are more income mobile than Americans. However, when income mobility is measured by absolute movements in income, Americans are found to be more income mobile than members of former West German households.
Keywords: 330; Einkommensverteilung; Soziale Mobilität; Vergleich; USA; Deutschland